Effect of environmental parameters on the content and sugar composition of sulfated polysaccharides in some tropical seagrass - Nguyen, Vy Xuan; Nguyen Nhat, Nhu Thuy; Nguyen, Xuan Thuy; Le Ho, Khanh Hy; Pham, Duc Thinh; Dao, Viet Ha (Vietnam Journal of Marine Science and Technology, 2023)
Seagrasses are a paraphyletic group of marine angiosperms that evolved three to four times from land plants and returned to the sea. Halophila ovalis, Thalassia hemprichii and Enhalus acoroides (Hydrocharitaceae) are species that can occur in wide salinity ranges. Sulfated polysaccharides (SPs) comprise a complex group of macromolecules with many critical biological functions. We assume that SP may play a role in salt tolerance in seagrass. In this study, three seagrass species collected in both rainy and dry seasons from the fields were analyzed to determine the total SP contents and different functional groups of SP. Quantification of total SP was done by photometric assays. High-performance anion-exchange chromatography with Pulsed Electrochemical Detection (HPAEC) determined different functional groups of SPs. The results indicated higher total SP contents in seagrass are present in plants at higher salinities and environmental temperatures. The percent of functional groups of SPs are present in the following order: glucose > galactose > arabinose > mannose > rhamnose > fucose. The order is not different between the two seasons.